A critical overview of Scrophularia striata Boiss.: Phytochemical and pharmacological investigations - Mohammad Mehdi Zarshenas; Seyyed Sasan Mousavi; Tahereh Movahhed Haghighi (Elsevier, 2022)
Ethnopharmacological relevance, Scrophularia striata Boiss belongs to Scrophulariaceae family and grows in western parts of Iran. S. striata phytochemical and pharmacological data were compiled in this review. Scopus database searched for the term "Scrophularia striata" up to 1st September 2022. Various S. striata formulations were studied for antibacterial, antioxidant, insecticidal, and immunomodulatory properties in recent research, regarding reports on its ethnopharmacological applications. Several studies were published on the chemical composition of S. striata's different extracts. While many pharmacological and animal evaluations on antimicrobial, antioxidant, anticancer, antiparasitic, anti-inflammatory, and anxiolytic activities were done, and most assessments were centralized on wound healing and angiogenesis evaluations. While pharmacological and animal studies on antibacterial, antioxidant, anticancer, antiparasitic, anti-inflammatory, and anxiolytic properties were conducted, most of the research focused on wound healing and angiogenesis. This aspect focused on clinical practice and allied studies. On the other side, comprehensive studies on the toxicity, teratogenicity, and clinical effectiveness of S. striata, on the other hand, are lacking.